'Barbarising' China in American trade war discourse: the assault on Huawei. Issue 7 (6th July 2021) - Zhang, Yongjin
Abstract: How is the legitimation of the American trade war with China discursively managed and conferred in recent American political discourse? This paper critically examines this under-explored question in the current literature. Taking cues from critical international theory and its insight on discourse and foreign policy, I start by historicising the discursive practices, which I call 'barbarising China', in the construction of civilisation vs barbarism as a hierarchical opposition. Mapping authoritarian China onto this historically contingent liberal civilisational edifice, I argue, has prepared the ground for American political action in the trade war. Through a critical analysis of how China has been constructed as a 'barbarian' economic aggressor in recent American political discourse, I further argue that the 'political reality' and 'knowledge' this discursive practice produces serves not only the political imperative of legitimising American trade war policy choices, but also a particular need of the 'civilised' hegemon to legitimise its power and practices beyond the trade war. Through a close examination of a coordinated assault on Huawei, I illustrate how 'barbarising' China has been discursively done as an integral part of the trade war and assert that 'barbarising' China has become indispensable in American strategy to sustain its precarious hegemony.